Pendampingan Dan Pemberdayaan Guru PAUD Dalam Pembelajaran Kurikulum Merdeka Dengan E-Siroh Nabawiyyah Untuk Mencapai Pembentukan Karakter Pancasila Anak Usia Dini - Kurnia Pratiwi, Ratri (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
This service focuses on assisting and empowering PAUD teachers in implementing the Independent Curriculum through e-Siroh Nabawiyyah to support the formation of Pancasila character in early childhood. This program aims to provide training to PAUD teachers so they can integrate the values ​​in the Siroh of the Prophet Muhammad SAW as part of a learning process based on the character of Pancasila. The assistance provided includes understanding the Merdeka Curriculum and using the e-Siroh Nabawiyyah application, making it easier for teachers to deliver material in an interactive and engaging way. The service method uses the ABCD approach. The steps consist of the 5-D cycle (Define, Discovery, Dream, Design, and Destiny). The assistance results show several competencies obtained by the assisted communities (RA Raudlatut Tholabah Jenggawah and TK Raudlatul Jannah Jenggawah) after the assistance was carried out, namely Pedagogical Abilities and Skills. Pedagogical abilities are demonstrated by student-oriented behaviour in preparing the Independent Learning Curriculum so that it can shape the Pancasila AUD character. Critical-thinking skills have ability dimensions, including a. Analysis of Learning Objectives; b. Selection of content (content and images) of textbooks; c. Content integration with technology. Meanwhile, skills are developing, namely technical capabilities in managing Nabawiyah e-search and forming Pancasila AUD Character.